The development of professional skills of the recent graduates of medical sciences - Oscar Mena Martín; Taimy Breijo Worosz; Odalys Orraca Castillo; Berkis Martínez Orraca (Revista de Ciencias Médicas de Pinar del Río, 2017)
Introduction: the professionalization of the recent graduate is one of the priorities, given the need of improving the ways of performance for competent professional graduates.